2012
DOI: 10.1080/02699931.2011.585069
|View full text |Cite
|
Sign up to set email alerts
|

Humour as emotion regulation: The differential consequences of negative versus positive humour

Abstract: Humour is often seen as an adaptive coping strategy; however, the empirical literature is inconclusive. One possible explanation is that different types of humour have different adaptive consequences. In the present research, we predicted that positive (good-natured) humour would be more effective at regulating negative emotions than negative (mean-spirited) humour. In Study 1, participants were shown negative pictures two times. First, they simply viewed the pictures and rated their levels of positive and neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
138
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(149 citation statements)
references
References 22 publications
6
138
0
5
Order By: Relevance
“…Various researches indicated that humor, when used in a positive manner, enhanced positive sentiments (Samson and Gross, 2012), enabled people to establish good relations (Banas, Dunbar, Rodriguez, and Liu, 20112;Özdemir, Sezgin, Kaya, and Recepoğlu, 2011), boosted employee motivation (Recepoğlu, Kılınç, and Çepni, 2011), lessened organizational tension, alleviated the employee's problems (Malone, 19800), and increased productivity (Avolio, Howell, and Sosik, 1999). If humor is used in a negative fashion, positive sentiments dwindle (Samson and Gross, 2012) while organizational loyalty among employees also fall (Romero and Arendt, 2011). It is also believed that humor also has a significant effect on negative behavior observed in educational organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Various researches indicated that humor, when used in a positive manner, enhanced positive sentiments (Samson and Gross, 2012), enabled people to establish good relations (Banas, Dunbar, Rodriguez, and Liu, 20112;Özdemir, Sezgin, Kaya, and Recepoğlu, 2011), boosted employee motivation (Recepoğlu, Kılınç, and Çepni, 2011), lessened organizational tension, alleviated the employee's problems (Malone, 19800), and increased productivity (Avolio, Howell, and Sosik, 1999). If humor is used in a negative fashion, positive sentiments dwindle (Samson and Gross, 2012) while organizational loyalty among employees also fall (Romero and Arendt, 2011). It is also believed that humor also has a significant effect on negative behavior observed in educational organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ES has been found to reduce self-reported amusement when carried out while watching amusing films (Gross & Levenson, 1997). Humor can also be used as an emotion-regulation strategy on its own (e.g., Samson & Gross, 2012). Importantly, exploring the neural bases of humor perception and of emotion regulation in response to (or via) humor may be of clinical relevance and contribute to the successful treatment of disorders involving alterations in humor perception and humor regulation.…”
mentioning
confidence: 99%
“…Humor has been regarded as a source of positive emotions, which can distract the individual from negative emotions and thus reduce said negative feelings (Samson & Gross, 2012). Apter and Smith (1977) theorize that humor can help individuals see a situation as less severe, and distance themselves from negative emotions.…”
Section: Humor and Its Relationship To Age And Lonelinessmentioning
confidence: 99%